A study on the effectiveness of user-generated content travel site towards potential tourist in Melaka / Nuramira Idris, Qairawani Zainal and Nurul Alia ‘Aqilah Hamdan - Idris, Nuramira; Zainal, Qairawani; Hamdan, Nurul Alia ‘Aqilah (2014)
Through social media applications, consumers are increasingly participating in information processes. When booking a journey, consumer opinions exchanged via modern media shape the reputation of enterprises like travel agencies and thus have a major impact on the decision to book a journey. User-Generated Content (UGC) such as online travel reviews written by travellers and posted to virtual communities are being used more frequently to communicate travel-related information. UGC is therefore helping travellers to make decisions about their travel. However, some people were discouraged to use UGC when planning their holiday due to untrusted with the information displayed. This study contributes to the further development of online travel site by determining the most preferable UGC in travel planning. The aim of this paper is to determine the effectiveness of UGC of travel media based on SMART Objective which are specific, measurable, achievable, relevant and time-bound. The significance of this study can be seen in term of management, academic and community / user’s perspective. Based on the SMART Objective, the most effective User-Generated Content (UGC) can be determined. Mostly people would prefer to use UGC as their medium in making reservation rather than using a manual reservation. This is because by using online reservation, their job will become easier and effective which can save time and money. The questionnaire was used in determining the result of this study aiming to 100 potential tourists around Bandar Hilir, Melaka. A close-ended question was used in the survey questionnaire. Several places have been chosen as a sample study due to the most famous place of interest. The survey was conducted in 2 days by approaching respondents to participate in this survey. All the data attained were keyed-in to the Statistical Package for the Social Science (SPSS) Windows version 21.0 for further analysis. The most preferable UGC were then determined at the end of this study. However, there was some limitation while conducting this study such as time constraint, sample size and unexpected situation that occurred. In conclusion, UGC is very important in determining decision for travel site, which makes the travel planner become more effective and relevant in the future.